The Role Of The Moral Dimensions Of The Financial Crisis In Strengthening Foreign Direct Investment In The Framework Of Investment Indicators Fulfillment - NOORULDEEN, PAYMAN MAMOON (Journal of Duhok University, 2019)
Given the importance of foreign direct investment in the economic and social development of countries, this research is looking for testing a new method for stating the foreign direct investment enhancement based on the ethical dimensions of the financial crisis through asking the question: How to regulate institutional and regulatory ethics that affect foreign investors' decisions and strengthen the mechanism of attracting their investments?     The research aims to address the theoretical framework of the financial crisis and direct foreign investment, then studying and analyzing foreign direct investment indicators that enhance its capabilities, through the logic that points to the importance of following personal, institutional and organizational ethics in order to support foreign direct investment, assuming that there is a significant correlation between the ethical dimensions of the financial crisis and the global investment indicators in the surveyed sample, as well as a significant effect to the dimensions of the financial crisis in the global investment indicators. Statistical analyzes, such as repetitive distributions, percentage ratios, and computational modes, and standard deviations of each of the main search variables were used to obtain a major result: there is a significant correlation relationship and a significant effect between the study variables. Research suggests the need to increase attention to ethics, especially the ethics of society, because they significantly affect the measurement of global investment indicators.